The Influence of Leadership and Competence on Employee Performance in the Employees’ Cooperative of PT. Indosat, Tbk., with Innovative Work Behavior as Mediation - Handaka, Puthut; Herawati, Aty (Dinasti International Journal of Management Science, 2024)
In the dynamic landscape of rapid changes and fierce competition, Innovation Work Behavior (IWB), along with effective leadership and employee competence, plays a crucial role in ensuring the survival and growth of cooperatives. This research examines the influence of leadership and competence on employee performance within the Employees’ Cooperative of PT. Indosat, Tbk., with innovative work behavior as a mediator. The study collected primary data using purposive sampling through a survey of 64 participants. Data analysis utilized the path analysis method to better understand the relationships between variables. The findings suggest that both leadership and competence significantly and directly impact Innovative Work Behavior (IWB). Furthermore, IWB directly enhances employee performance. Additionally, leadership and competence indirectly influence employee performance through their effect on IWB as a mediator.